The Landscape Contest at ICPR 2010 - Macià, Núria; Ho, Tin Kam; Orriols-Puig, Albert; Bernadó-Mansilla, Ester (Recognizing Patterns in Signals, Speech, Images and Videos, 2010)
The landscape contest provides a new and configurable framework to evaluate the robustness of supervised classification techniques and detect their limitations. By means of an evolutionary multiobjective optimization approach, artificial data sets are generated to cover reachable regions in different dimensions of data complexity space. Systematic comparison of a diverse set of classifiers highlights their merits as a function of data complexity. Detailed analysis of their comparative behavior in different regions of the space gives guidance to potential improvements of their performance. In this paper we describe the process of data generation and discuss performances of several well-known classifiers as well as the contestants’ classifiers over the obtained data sets.